Genetic analysis for type 1 diabetes genes in juvenile dermatomyositis unveils genetic disease overlap. (16th February 2022) - Qu, Hui-Qi; Qu, Jingchun; Vaccaro, Courtney; Chang, Xiao; Mentch, Frank; Li, Jin; Mafra, Fernanda; Nguyen, Kenny; Gonzalez, Michael; March, Michael; Pellegrino, Renata; Glessner, Joseph; et al.
Abstract: Objectives: JDM is a serious autoimmune and complex genetic disease. Another autoimmune genetic disease, type 1 diabetes (T1D), has been observed for significantly increased prevalence in families with JDM, while increased JDM risk has also been observed in T1D cases. This study aimed to study whether these two autoimmune diseases, JDM and T1D, share common genetic susceptibility. Methods: From 169 JDM families, 121 unrelated cases with European ancestry (EA) were identified by genome-wide genotyping, principal component analysis and identical-by-descent (IBD) analysis. T1D genetic risk score (GRS) were calculated in these cases and were compared with 361 EA T1D cases and 1943 non-diabetes EA controls. A total of 113 cases of the 121 unrelated European cases were sequenced by whole exome sequencing. Results: We observed increased T1D GRS in JDM cases ( P  = 9.42E-05). Using whole exome sequencing, we uncovered the T1D genes, phospholipase B1, cystic fibrosis transmembrane conductance regulator, tyrosine hydroxylase, CD6 molecule, perforin 1 and dynein axonemal heavy chain 2, potentially associated with JDM by the burden test of rare functional coding variants. Conclusion: Novel mechanisms of JDM related to these T1D genes are suggested by this study, which may imply novel therapeutic targets for JDM and warrant further study.